Sex Hormone-Binding Globulin (SHBG) Reduction: The Alarm Bell for the Risk of Non-Alcoholic Fatty Liver Disease in Adolescents with Polycystic Ovary Syndrome - Flavia Urbano; Mariangela Chiarito; Crescenza Lattanzio; Angela Messa; Marco Ferrante; Mariantonietta Francavilla; Irsida Mehmeti; Giuseppe Lassandro; Paola Giordano; Maria Felicia Faienza (Children, 2022)
Polycystic ovary syndrome (PCOS) represents an endocrine condition affecting 5–18% of adolescents, frequently in association with obesity, metabolic alterations, and liver dysfunction. In this study, we aimed to evaluate the prevalence and risk factors for developing non-alcoholic fatty liver disease (NAFLD) in a cohort of PCOS adolescents. Thirty-two girls were assessed for anthropometric and biochemical markers: total cholesterol (TC), high density lipoprotein cholesterol (HDL-C), low density lipoprotein cholesterol (LDL-C), triglycerides (TG), glucose, insulin, alanine aminotransferase (ALT), aspartate aminotransferase (AST) and gamma glutamyl transpeptidase (γGT). In addition, LH, FSH, 17β-Estradiol (E2), prolactin, testosterone (T), free testosterone, delta 4-androstenedione (D4 A), dehydroepiandrosterone sulfate (DHEAS) and sex hormone binding protein (SHBG) were also evaluated. All subjects underwent liver ultrasound to detect NAFLD. Our data demonstrated that PCOS adolescents complicated with NAFLD accounted for 37.5%, and those with obesity and lower SHBG were more predisposed to developing NAFLD. Moreover, SHBG showed a negative correlation with several parameters such as blood pressure, body mass index, waist circumference, insulin, and the homeostatic model assessment of insulin resistance (HOMA-IR). Our results demonstrated that the assessment of SHBG may allow the identification of PCOS adolescents at risk for developing NAFLD and metabolic alterations.